Epidemiological Survey of Knowledge, Attitudes, and Health Literacy Concerning Mental Illness in a National Community Sample - Suhaila Ghuloum PhD; Abdulbari Bener PhD, FRSS, FFPH; F. Tuna Burgut MD (SAGE Publishing, 2010)
The aim of this study was to examine the knowledge, attitudes, and practices concerning mental illness among Qatari and other Arab expatriates. Method: This is a cross-sectional survey conducted from October 2008 to March 2009. A questionnaire was designed to assess knowledge, attitude, and practice regarding mental illness. Results: Of 2254 subjects surveyed, 49.6% were Qataris, 50.4% other Arab expatriates, 54.8% males, and 45.2% females. A majority of the respondents thought that substance abuse like alcohol or drugs could result in mental illness (84.7%). Fewer than half of the subjects believed that mentally ill people are mentally retarded (40.6%). 48.3% believed that mental illness could result from punishment from God. The most common information source on mental illness was media (64.2%). Recognition of common mental disorders in the studied population was poor (72.5%). Conclusion: Knowledge of mental illness among the Arabic-speaking population of Qatar was quite poor.